Mutagenesis effect using gamma ray radiation on morphological changes, productivity, and genetic variation in Chloris Gayana cv. Callide - Aini Nindyaresmi; Nafiatul Umami; Asih Kurniawati; Rini Anggriani; Agussalim; Mohammad Mijanur Rahman (UPM Press, 2024)
Chloris gayana grass is a perennial tropical grass that is highly adaptable and resistant to climate change. As a cover crop, this grass can improve soil conditions. This grass has high palatability and potential to be improved through breeding to enhance the quality and productivity of ruminants’ feed. This research was conducted to determine the effect of gamma ray radiation on the morphology, productivity and genetic variation of C. gayana cv. Callide. This research used 4 radiation doses of 0, 75, 150 and 225 Gy, which were given to C. gayana cv Callide plant seeds via a Gamma 60Co irradiator chamber. A radiation dose of 150 Gy was proven to increase the development of culm diameter (p < 0.05). The best productivity was shown by radiation doses of 75 and 150 Gy, which increased the production of fresh, dry, and organic matter. The results of genetic variation analysis using Random Amplified Polymorphic Deoxyribonucleic Acid Polymerase Chain Reaction (RAPD PCR) showed that the polymorphism resulting from using the Organophosphate Degradation (OPD) 8 primer was 66.67%, and the OPD 11 primer was 62.50%. Overall, gamma ray radiation with 75 and 150 Gy doses on C. gayana cv. Callide has been proven to improve plant productivity.